Evidence for Short Temporal Atmospheric Variations Observed by Infrasonic Signals: 2. The Stratosphere. Issue 10 (13th October 2022) - Averbuch, G.; Sabatini, R.; Arrowsmith, S.
Abstract: This study uses infrasound detections from a repetitive source to estimate the effect of the atmosphere's temporal variability on infrasound. While a previous paper focused on infrasound propagation through the troposphere to a distance of 54 km, this study uses stratospheric returns detected 256 km from the source. Based on source‐receiver pairs, the empirical Green's function is calculated every 20 s for 52 events; these allow generating a set of synthetic signals where variations are ascribed to variation in the atmosphere. In addition, observations are compared with numerical simulation results based on realistic atmospheric conditions. Results show that variations of stratospheric infrasound signals are observed over timescales ranging from tens of seconds to minutes and have dominant periods ranging from tens to hundreds of seconds. These results motivate using infrasound to probe short temporal changes in the middle atmosphere and study their underlying phenomena. Key Points: Evidence for temporal (minute‐scale) variability of the middle atmosphere is observed by infrasound Short temporal dynamics affects infrasonic phases, waveforms, propagation time, and energy The same atmospheric phenomena drive variations of infrasonic correlation coefficient and energy